Pengaruh Consumer Satisfaction, Brand Image Dan Trust Terhadap Consumer Loyalty Pada Pt. Kai (Persero) Daop 9 Jember Stasiun Probolinggo - Nursafitri, Ike; Priantono, Seger; Rahajeng, Yekti (JUMAD : Journal Management, Accounting, & Digital Business, 2024)
Use The aim of this research is to determine the partial influence of consumer satisfaction, brand image and trust on consumer loyalty at PT. ΚΑΙ (Persero) DAOP 9 Jember Probolinggo Station. The type of research used is causal associative with a quantitative approach. The population in this study is consumers of the DAOP 9 Jember Train, Probolinggo Station in February-March 2024. The number of samples in this study was 100 samples obtained from the Slovin formula calculation. In proving and analyzing this, the convergent validity test, discriminant validity test, reliability test, r-square test, q-square test and hypothesis test are used.Partial test results show that Consumer Satisfaction (X1) with 1 statistic of (3.608) or p value (0.000 < 0.05), then H0 can be accepted or has a significant effect. Brand Image (X2) with a t statistic of (3.772) or p value (0.440 > 0.05), then H0 is not proven or has no significant effect. Trust (X3) with a t statistic of (1.387) or p value (0.167>0.05), then HO is not proven or has no significant effect.